Operating Room WHO Surgical Safety Checklist Process Completion: An Observational Study - Bhattarai, Prajjwal Raj; Khadka, Bikash; Sharma, Apurb; Adhikari, Hemant; Pradhan, Kushal; Thapa, Kristi; Singh, Rohit Man (Nepal Mediciti Medical Journal, 2025)
BACKGROUND The World Health Organization (WHO) Surgical Safety Checklist (SSC) is used globally to ensure patient safety during surgery. Two years after its implementation in the Nepal Mediciti’s operating room (OR), adherence to the protocol was evaluated with mixed-method observational study.METHODS Data collection was on-site non-participant observations of Team WHO checklist completion conduction in the OR. Medical records were also audited. SPSS was used for data analysis.RESULTS The mean number of personnel in the OR was 7. Sign In was not conducted in 3.8% of cases, whereas surgeon unavailability during Sign In was 15%. In 18.2% of cases, antibiotics were administered more than an hour before induction time. In 10.4% of cases, Time Out was not conducted on time prior to surgical incision. Team introduction by name and role was very poor (15.3%). In 26% of cases, sign-out was not conducted. Actual blood loss matched predicted blood loss in 93.6% of cases, whereas the surgeon recorded only 73.4% of matches for actual and predicted surgical duration. On memory assistance, 13.3% of checklist completion was carried out. Factors such as inadequate staff, negative attitude towards the checklist completion and hesitance, and a lack of teamwork hindered its implementation.CONCLUSION The unavailability of key OR team members during sign-in and sign-out time was the most common reason for the omission or partial use of the SSC. The implementation of the surgical safety checklist will upgrade patient safety measures, combine teamwork abilities, and enhance departmental culture locally.